Energy and emission analysis for industrial motors in Malaysia - Saidur, Rahman; Rahim, N.A.; Ping, H.W.; Jahirul, M.I.; Mekhilef, Saad; Masjuki, Haji Hassan (Elsevier, 2009)
The industrial sector is the largest user of energy in Malaysia. Industrial motors account for a major segment of total industrial energy use. Since motors are the principle energy users, different energy savings strategies have been applied to reduce their energy consumption and associated emissions released into the atmosphere. These strategies include using highly efficient motors, variable speed drive (VSD), and capacitor banks to improve the power factor. It has been estimated that there can be a total energy savings of 1765, 2703 and 3605 MWh by utilizing energy-efficient motors for 50, 75 and 100 loads, respectively. It was also found that for different motor loads, an estimated US115,936 US173,019 and US230,693 can be saved in anticipated energy costs. Similarly, it is hypothesized that a significant amount of energy can be saved using VSD and capacitor banks to reduce speed and improve the power factor, thus cutting energy costs. Moreover, a substantial reduction in the amount of emissions can be effected together with the associated energy savings for different energy savings strategies. In addition, the payback period for different energy savings strategies has been found to be reasonable in some cases.